2012
DOI: 10.1128/jvi.05308-11
|View full text |Cite
|
Sign up to set email alerts
|

Viral Adaptation to Host Immune Responses Occurs in Chronic Hepatitis B Virus (HBV) Infection, and Adaptation Is Greatest in HBV e Antigen-Negative Disease

Abstract: Hepatitis B virus (HBV)-specific T-cell responses are important in the natural history of HBV infection. The number of known HBV-specific T-cell epitopes is limited, and it is not clear whether viral evolution occurs in chronic HBV infection.We aimed to identify novel HBV T-cell epitopes by examining the relationship between HBV sequence variation and the human leukocyte antigen (HLA) type in a large prospective clinic-based cohort of Asian patients with chronic HBV infection recruited in Australia and China (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Previous study revealed that interleukin-17-producing CD4+ T cells (Th17) are highly enriched in both peripheral blood and liver and correlate with severity of liver damage in patients with CHB 27. Several studies had identified HLA-DRB1 alleles-specific hepatitis B virus epitopes and CD4+ T-cell responses 28 29. By ex vivo stimulation of HBV epitopes, we did find the HLA-DRB1*12:02 - restricted CD4+ T-cell responses in a patient with CHB with HLA-DRB1*12:02 / DRB1*13:12 genotype (see online supplementary figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that interleukin-17-producing CD4+ T cells (Th17) are highly enriched in both peripheral blood and liver and correlate with severity of liver damage in patients with CHB 27. Several studies had identified HLA-DRB1 alleles-specific hepatitis B virus epitopes and CD4+ T-cell responses 28 29. By ex vivo stimulation of HBV epitopes, we did find the HLA-DRB1*12:02 - restricted CD4+ T-cell responses in a patient with CHB with HLA-DRB1*12:02 / DRB1*13:12 genotype (see online supplementary figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…An insufficient and persistent antiviral immune reaction contributes to HBV mutations during HBV evolution. The HBV mutations, to some extent, were consequences of viral adaptation to the host immune responses (51). Further experimental and prospective population-based studies are warranted to clarify the roles of HLA-DPA1 and HLA-DPB1 in HBV evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial immunotolerant phase, viral load is high, hepatitis B e antigen (HBeAg) is positive. With the progression of chronic infection, HBV mutations gradually occur, especially during HBeAg seroconversion [6][7][8][9]. HBV accumulates mutations via minimizing the epitopes recognized by CD8 + T cells, particularly in the enhancer II/basal core promoter/precore (EnhII/BCP/preC) region and the preS/S regions.…”
Section: Introductionmentioning
confidence: 99%